CARING ECONOMICS LEARNING TO DEVELOP CARING ATTITUDE AMONG HIGH SCHOOL STUDENTS - Wahyuni, Daru; Djatmika, Ery Tri; Widjaya, Sri Umi Mintarti; Wahyono, Hari (LPMPP Universitas Negeri Yogyakarta, 2021)
Even though economics learning in Senior High Schools has been able to increase students’ economic knowledge, their economic behavior is still far from being appropriate, whereas their concern for others, the environment, and even for themselves is lacking. The aims of this study were to apply caring economics learning (CEL) at senior high schools in Indonesia and to observe the internalization of caring economics attitude among the students through action research. It contained instructional package consisting of lesson plans, student worksheets, instructional materials, instructional media, and learning assessment in the form of situational judgment tests (SJTs). The CEL employed case method that was implemented in three learning activities. The data were obtained through observation, interviews, tests, and documentation. The study has revealed that the CEL was assessed by the observers as good and excellent. The success of caring attitude development on the students was reflected in the number of students showing caring attitudes, which increased from the first learning activity (52%) to the last one (95%). Based on the SJT-1, 55.56% of students achieved high scores and 44.44% had moderate scores. Based on the SJT-2, the number of students with high scores increased significantly (77.78%), while the number of students who had moderate scores decreased considerably (22.22%).